Understanding factors influencing adoption of air pollution protective measures using the knowledge-attitude-behavior model - Ying-Jhen Huang; Ping-Hsien Lee; Shu-Hui Hsieh; Yu-Chan Chiu; Ta-Chien Chan (Scientific Reports)
Abstract To address air pollution hazards effectively, it is crucial to understand the factors that influence residents’ adoption of harm reduction measures. Existing studies often focus on passive defense and ignore active strategies such as air purifiers, dehumidifiers, anti-haze window screens, and air-purifying plants. This study adopted the Knowledge–Attitude–Behavior (KAB) model to explore the factors that influence residents to take proactive measures to prevent the impacts of air pollution. This cross-sectional study recruited 371 participants aged 25–64 years living in southern Taiwan. A one-shot online survey was conducted to examine demographic information, air pollution exposure experience, knowledge, risk perceptions, attitudes toward air pollution protective measures, perceived barriers and benefits, payment for protective measures, and actual engagement in protective actions. Structural equation modeling was used to examine the relationships among these factors. This study reveals that the adoption of these protective measures can be understood through three primary pathways. The first pathway linked knowledge to attitude toward behavior. Regarding the various protective measures, this study found that knowledge strongly influenced individuals’ attitudes. This, in turn, influenced their likelihood of engaging in protective measures. The second pathway revealed the effect of risk perception on protective measures, with attitudes mediating this relationship. Perceived risk susceptibility and risk severity were linked to attitudes, which further influenced the adoption of protective measures. The third pathway emphasized the direct effects of perceived barriers on the adoption of protective measures. Individuals who perceived fewer barriers were more likely to adopt these measures. This study fills the gap in the understanding of the factors influencing residents’ adoption of proactive air pollution protection measures. Moreover, this study underscores the importance of increasing public awareness and reducing barriers to promote individual actions for mitigating the negative effects of air pollution.